Effects of orally administered Bdellovibrio bacteriovorus on the well-being and Salmonella colonization of young chicks - Atterbury, Robert J.; Hobley, Laura; Till, Robert; Lambert, Carey; Capeness, Michael J.; Lerner, Thomas R.; Fenton, Andrew K.; Barrow, Paul; Sockett, R. Elizabeth (American Society for Microbiology., 2011)
Bdellovibrio bacteriovorus is a bacterium which preys upon and kills Gram-negative bacteria, including the zoonotic pathogens Escherichia coli and Salmonella. Bdellovibrio has potential as a biocontrol agent, but no reports of it being tested in living animals have been published, and no data on whether Bdellovibrio might spread between animals are available. In this study, we tried to fill this knowledge gap, using B. bacteriovorus HD100 doses in poultry with a normal gut microbiota or predosed with a colonizing Salmonella strain. In both cases, Bdellovibrio was dosed orally along with antacids. After dosing non-Salmonella-infected birds with Bdellovibrio, we measured the health and well-being of the birds and any changes in their gut pathology and culturable microbiota, finding that although a Bdellovibrio dose at 2 days of age altered the overall diversity of the natural gut microbiota in 28-day-old birds, there were no adverse effects on their growth and well-being. Drinking water and fecal matter from the pens in which the birds were housed as groups showed no contamination by Bdellovibrio after dosing. Predatory Bdellovibrio orally administered to birds that had been predosed with a gut-colonizing Salmonella enterica serovar Enteritidis phage type 4 strain (an important zoonotic pathogen) significantly reduced Salmonella numbers in bird gut cecal contents and reduced abnormal cecal morphology, indicating reduced cecal inflammation, compared to the ceca of the untreated controls or a nonpredatory ΔpilA strain, suggesting that these effects were due to predatory action. This work is a first step to applying Bdellovibrio therapeutically for other animal, and possibly human, infections.